Influence of Working Pressure on Ion Sensitive Probe Measurement in Microwave ECR Plasmas - 马志斌 吴俊 谭必松 沈武林 潘鑫 汪建华 (Plasma science & technology, 2015)
In order to precisely measure the ion parameters in a microwave electron cyclotron resonance plasma using an ion sensitive probe,the dependences of the current-voltage（I-V）characteristics on the shielding height（h）and the potential difference between inner and outer electrodes（V_B）have been investigated at different working pressures of 0.03 Pa and 0.8 Pa.Results show that the I-V curves at higher pressure are more sensitive to the variation of h than those at lower pressure.The influence of V_B on ion temperature（T_i）measurement becomes more prominent when the pressure is increased from 0.03 Pa to 0.8 Pa.Under both pressures,the optimized h is obtained at the condition where the current reaches zero in the positive voltage region with a suitable V_B of-1.5 V because of effective shielding of the electron E×B drift.